Study of the genus Bracon Fabricius, 1804 (Hymenoptera: Braconidae) from Iran: new subspecies, new records and an updated checklist - Zargar, Mohammad; Samartsev, Konstantin; Talebi, Ali Asghar; Farahani, Samira (Zootaxa, 2020)
The present study is based on the genus Bracon Fabricius collected from the Khuzestan province in the southwestern part of Iran during 2016–2017. In total, 35 species including one subspecies were collected and identified, of which 10 species are recorded for the first time from Iran and Bracon (Osculobracon) pelliger rumezensis Samartsev & Zargar ssp. n. is described. In addition, 24 species are recorded for the first time from Khuzestan province in southwestern Iran. Brief diagnoses with illustrations for new records from Iran and a faunistic list with distribution data are provided.